Assessing engineering students' attitudes towards corporate social responsibility principles - Saari, Ulla A. (TAYLOR & FRANCIS LTD, 2025)
Ethical and sustainable thinking is an important competence in the engineering education to support students' abilities to act and perform in a responsible manner in corporate contexts, and consequently contribute to a sustainable future. This paper investigates engineering students' attitudes towards ethical and sustainable thinking focusing on the corporate social responsibility (CSR) principles in the context of entrepreneurship courses as a part of larger research project. Engineering students from a Finnish and an Estonian university (N = 342) responded to a self-assessment survey. The students' attitudes towards CSR principles were assessed both on the enterprise level and the individual level as expectations of potential future employees. The findings indicate that engineering students acknowledge the need to take into account responsible thinking and that it is important for enterprises to be both socially and environmentally responsible in their activities. The self-assessment tool of ethical and sustainable thinking associated with the entrepreneurship competence model and CSR principles can be helpful in practice when university teachers wish to support and assess their students' attitudes towards CSR principles among other entrepreneurship competencies when creating new course content.